Epidemiologi Hawar Daun Bibit Pinus Merkusii yang Disebabkan oleh Pestalotia theae - Sutarman; Hadi, Soetrisno; Saefuddin, Asep; Achmad; Suryani, Ani (Jurnal Manajemen Hutan Tropika, 2004)
The objectives of the study are as follows: to know the interrelationships between the weather components as well as Pestalotia theae's aerial conidiospore population and the development of needle blight on Pinus merkusii seedlings, and to determine the effect of nursery site on the early development of the disease. Two week's average without interval model is the most reliable model to be used for determining the interrelationship between the development of the disease severity and the weather components. Light duration, rain fall, relative humidity and temperature are the weather components significantly affect the increase of the disease severity. The nursery in Pongpoklandak, Cianjur (26,5 - 30,5 oC; RH: 92-98 %), West Java, is the most optimal location for the development of the disease. To maintain the Disease Index at the most about 25 on seedlings over 6 months old, is the key factor for the successful management of needle blight on P. merkusii seedlings in the nursery.